Unraveling the Role of Ubiquitin-Conjugating Enzyme UBE2T in Tumorigenesis: A Comprehensive Review - Chang Gao; Yan-Jun Liu; Jing Yu; Ran Wang; Jin-Jin Shi; Ru-Yi Chen; Guan-Jun Yang; Jiong Chen (Cells)
Ubiquitin-conjugating enzyme E2 T (UBE2T) is a crucial E2 enzyme in the ubiquitin-proteasome system (UPS), playing a significant role in the ubiquitination of proteins and influencing a wide range of cellular processes, including proliferation, differentiation, apoptosis, invasion, and metabolism. Its overexpression has been implicated in various malignancies, such as lung adenocarcinoma, gastric cancer, pancreatic cancer, liver cancer, and ovarian cancer, where it correlates strongly with disease progression. UBE2T facilitates tumorigenesis and malignant behaviors by mediating essential functions such as DNA repair, apoptosis, cell cycle regulation, and the activation of oncogenic signaling pathways. High levels of UBE2T expression are associated with poor survival outcomes, highlighting its potential as a molecular biomarker for cancer prognosis. Increasing evidence suggests that UBE2T acts as an oncogene and could serve as a promising therapeutic target in cancer treatment. This review aims to provide a detailed overview of UBE2T’s structure, functions, and molecular mechanisms involved in cancer progression as well as recent developments in UBE2T-targeted inhibitors. Such insights may pave the way for novel strategies in cancer diagnosis and treatment, enhancing our understanding of UBE2T’s role in cancer biology and supporting the development of innovative therapeutic approaches.